Insects on pig carcasses as a model for predictor of death interval in forensic medicine (Faculty of Medicine Universitas Indonesia, 2015)
Background: Forensic entomology has not been acknowledged in Indonesia so far. Indonesian carrion insects are very rarely reported. The aim of this study was to obtain the types of insects on pig carcasses that could be used for the estimation of post-mortem interval.Methods: Four domestic pigs sacrificed with different methods were used as a model. The carcasses were observed twice daily (around 9 a.m and 4 p.m) during 15 days to assess the stages of decomposition and to collect insects, both in mature and immature stages. The immature insects were reared and the mature insects were indentified in the Laboratory of Pests and Plant Diseases, University of Sam Ratulangi, Manado. Chrysomya megacephala and C. rufifacies were identified both morphologically and with deoxyribose-nucleic acid (DNA) techniques.Results: Five stages of decomposition (fresh, bloated, active decay, post-decay, and skeletonization) were observed. A total of 11 Diptera and 8 Coleoptera species were found during a 15-days succession study. Chrysomya megacephala, C. rufifacies and Hermetia illucens colonized in all carcasses.Conclusion: Insects found on four different pig carcasses consisted mainly of widespread Diptera and Coleoptera. Chrysomya megacephala, C. rufifacies and Hermetia illucens seemed to be primary candidates for the estimation of the post-mortem interval.